Effect of molybdenum and tungsten on the activity of Mo-hydroxylases and the antioxidant system in plants - Mambetova, M.K.; Beisekova, M.K.; Kurmanbayeva, A.B.; Samat, A.; Bekturova, A.Zh.; Zhangazin , S.B.; Iksat, N.N.; Akbassova , A.Zh.; Masalimov, Zh.k. (Eurasian Journal of Applied Biotechnology, 2025)
Modern studies in the field of plant molecular biology pay considerable attention to the mechanisms of regulation of the antioxidant system. In this work we study the effect of heavy metals molybdenum and tungsten on the modulation of molybdenum-containing hydroxylases (Mo-hydroxylases) and the functioning of the antioxidant system of plants using the model organism Nicotiana benthamiana. The aim of the study is to analyse the effects of molybdenum and tungsten on the activity of antioxidant enzymes (SOD, CAT) as well as the Mo-enzymes aldehyde oxidase (AO) and xanthine dehydrogenase (XDH). The methods used include native gel electrophoresis and spectrophotometry. The main results show that molybdenum application promotes the activation of plant antioxidant system by increasing the production of reactive oxygen species (ROS) and superoxide dismutase (SOD) enzyme activities, while catalase activity changed insignificantly. Also, AO activity increased, whereas XDH activity was almost unchanged. On the contrary, tungsten application reduced the activity of these antioxidant defence mechanisms and inhibited Mo-hydroxylases. The practical significance of the work lies in the possibility of developing biotechnological approaches to increase plant resistance to abiotic stresses by regulating the activity of Mo-hydroxylases. The obtained data can be used in crop production and agriculture to improve stress tolerance of agricultural crops.